Problems and prospects of development and application of risk management software from point of view of quality management systems - E. S. Ryaryaeva; A. V. Agapov (Омский научный вестник)
The article deals with the development and application of software (software) «Solomka» for risk management of quality management systems (QMS). The problems and prospects of its application from the standpoint of management systems are highlighted. This topic will be of interest to specialists in the field of standardization and certification. The characteristic features of the application of the process and risk-oriented approaches in the construction and maintenance of management systems are highlighted and described. This article provides an analysis of user requirements for QMS risk management software, as well as a market research of proposals for similar software with a description of the advantages and disadvantages of each. This article provides an analysis of user requirements for QMS risk management software, as well as a market research of proposals for similar software with a description of the advantages and disadvantages of each. As a result of the work, the terms of reference for the development of software for risk management of QMS processes were substantiated, and user requirements for software were identified.